(untitled) (Fiep Bulletin - online, 2011)
This article analyzes the emergence and development of the two most important football clubs in the town of Novo Hamburgo, which is in one of the most important regions of German colonization and of industrialization in the Southernmost Brazilian state of Rio Grande do Sul. The growth of the town and of its football clubs, within the context of industrialization, was matched by the rivalry between its two main football clubs, namely Sport Club Novo Hamburgo founded in 1911 and Foot-Ball Club Esperança founded in 1914, established on a local basis. The article also analyzes this rivalry through the lens of the intense industrial development that Novo Hamburgo underwent during the period between 1911 and 1964, taking into consideration the principles that created the conditions for a qualitative leap from informal football towards association football and the clash between the oldest part of the town, which was the cradle of its foundation, and the central zone, which became the mainstay of the local industrial process.